Dermatological Disorders following Liver Transplantation: An Update - Dipesh Kumar Yadav; Xue li Bai; Tingbo Liang (Canadian Journal of Gastroenterology and Hepatology)
Patients undergoing liver transplantation (LT) are at a high risk of dermatological complications compared to the general population as a result of long-term use of immunosuppressant. However, the risk is not as high as other solid organ transplantations (SOT), particularly for skin cancer. The liver is considered as an immune privileged organ since it has a low prevalence of humoral rejection in contrast to other SOT, and thus, LT requires a minimal amount of immunosuppressants compared to other SOT recipients. However, because of the large volume of the liver, patients with LT have higher donor lymphocytes that sometimes may trigger graft-versus-host-disease, yet it is rare. On the other hand, the vast majority of the nonspecific dermatological lesions linked with cirrhosis improve after removal of diseased liver or due to the immunosuppressant used after LT. Nevertheless, dermatological infections related to bacteria, viruses, and fungus after LT are not uncommon. Additionally, the incidence of IgE-mediated food allergies develops in 12.2% of LT patients and may present as life-threatening conditions such as urticaria and/or angioedema and hypersensitivity. Moreover, skin malignancies after LT are a matter of concern. Thus, posttransplant dermatological care should be provided to all LT patients for any suspicious dermatological lesions. Our goal is to give an outline of the dermatological manifestation associated with LT for the clinicians by collecting the published data from all archived case reports.